A Quasi-Experimental Study of Gratitude Journaling on Students’ Academic Resilience - Ross, Hanna Oktasya; Hasanah, Megawatul; Roidah, Wintan; Raisatunnisa, Raisatunnisa; Russandari, Salsa Maulidya Nur; Hanifah, Aisyah; Qudsyi, Hazhira (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to analyze the effect of gratitude journaling in increasing students’ academic resilience. This quasi-experimental study used a non-randomized pretest-posttest with a control group design. The subjects were 16 students divided into two groups, 8 students in the experimental group and 8 students in the control group. The data collection instrument was questionnaires containing an academic resilience scale and a gratitude questionnaire. Then the data were analyzed using non-parametric statistical analysis with the Mann Whitney U Test and the Wilcoxon Signed Rank Test. The results of this study indicate that there is a significant difference between the experimental group that received the gratitude journaling treatment and the control group without receiving the gratitude journaling treatment (p = 0.035). Then, there is a significant difference in the level of academic resilience of the experimental group between before and after the treatment in the form of gratitude journaling (p = 0.017). Besides, the effect size score is 52.5%. This shows that gratitude journaling increases the student’s academic resilience with a moderate category. This research can fill in the gap in the study of gratitude and academic resilience based on experiments in Indonesia that have never existed before.